Contribution of 3D modelling and printing to learning in primary schools: a case study with visually impaired students from an inclusive Biology classroom - Anđić, Branko; Lavicza, Zsolt; Ulbrich, Eva; Cvjetićanin, Stanko; Petrović, Filip; Maričić, Mirjana (Journal of biological education, 2024)
Contemporary education adopts various new visualisation techniques for content to be learned. Recently, research on the application of 3D modelling and printing (3DMP) has been expanding. However, as the latest literature reviews indicate, little research is available on the contribution of 3DMP to learning of students with blindness (SWB) and students without disabilities (SWOD). This research aims to fill the gap through an exploratory case study, conducted in an inclusive Biology classroom in a primary school. Eight SWOD and four SWB (12 years old) participated in the study. The focus of the research was on pre-interventional and post-interventional students' knowledge about cells, and students' views on using 3DMP in Biology education. The data was analysed using Grounded Theory. The results indicate that 3DMP contributes to students' learning by improving the ability to enumerate, describe, and visualise the cell and its parts, by remediating some of the students' misconceptions and by increasing communication within a classroom. In terms of encountered obstacles, SWB noted that the quality of 3D models could cause new misconceptions. Adjusting the ratio, positioning and scaling of printed objects, inaccuracy in printing, and long printing process, are some of the problems which students encounter in 3DMP.